Pea protein-inulin conjugate prepared by atmospheric pressure plasma jet combined with glycosylation: structure and emulsifying properties - Ji, Hongfang; Wang, Qingqing; Wang, Xuefei; Zhang, Lingwen; Yang, Ping (Frontiers in Nutrition, 2024)
Pea protein is one of plant proteins with high nutritional value, but its lower solubility and poor emulsifying properties limit its application in food industry.Based on wet-heating glycosylation of pea protein and inulin, effects of discharge power of atmospheric pressure plasma jet (APPJ) on structure, solubility, and emulsifying ability of pea protein-inulin glycosylation conjugate were explored.Results indicated that the APPJ discharge power did not affect the primary structure of pea protein. However, changes in secondary and spatial structure of pea protein were observed. When APPJ discharge power was 600 W, the solubility of glycosylation conjugate was 75.0% and the emulsifying stability index was 98.9 min, which increased by 14.85% and 21.95% than that of only glycosylation sample, respectively. These findings could provide technical support for APPJ treatment combination with glycosylation to enhance the physicochemical properties of plant-based proteins.